2019
DOI: 10.1111/age.12852
|View full text |Cite
|
Sign up to set email alerts
|

Two linked TBXT (brachyury) gene polymorphisms are associated with the tailless phenotype in fat‐rumped sheep

Abstract: Summary T‐box transcription factor T (TBXT), encoding the brachyury protein, is an embryonic nuclear transcription factor involved in mesoderm formation and differentiation. Previous studies indicate that TBXT mutations are responsible for the tailless or short‐tailed phenotype of many vertebrates. To verify whether the tailless phenotype in fat‐rumped sheep is associated with TBXT mutations, exon 2 of the TBXT gene for 301 individuals belonging to 13 Chinese and Iranian sheep breeds was directly sequenced. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Deformed vertebrae were also observed in several tailless individuals, suggesting a regulatory function of the determined mutation in tail conformation. Han et al (2019) also confirmed the Chr8:87804589G>T missense mutation in fat-rumped sheep breeds with typically fewer caudal vertebrae (Han et al 2019). The study analyzed many samples from sheep with various tail phenotypes (~681 samples obtained through direct sequencing using the point mutation region or by extracting sequencing data deposited in databases) (Han et al 2019).…”
Section: Bmp2 As a Potential Candidate Gene For The Sheep Fattail Phe...mentioning
confidence: 58%
See 4 more Smart Citations
“…Deformed vertebrae were also observed in several tailless individuals, suggesting a regulatory function of the determined mutation in tail conformation. Han et al (2019) also confirmed the Chr8:87804589G>T missense mutation in fat-rumped sheep breeds with typically fewer caudal vertebrae (Han et al 2019). The study analyzed many samples from sheep with various tail phenotypes (~681 samples obtained through direct sequencing using the point mutation region or by extracting sequencing data deposited in databases) (Han et al 2019).…”
Section: Bmp2 As a Potential Candidate Gene For The Sheep Fattail Phe...mentioning
confidence: 58%
“…(2019) also confirmed the Chr8:87804589G>T missense mutation in fat‐rumped sheep breeds with typically fewer caudal vertebrae (Han et␣al . 2019). The study analyzed many samples from sheep with various tail phenotypes (˜681 samples obtained through direct sequencing using the point mutation region or by extracting sequencing data deposited in databases) (Han et␣al .…”
Section: Telling the Tale Of Tail In Sheep: Genomic Insightsmentioning
confidence: 64%
See 3 more Smart Citations